Design and performance of the field cage for the XENONnT experiment - Aprile, Elena; Abe, K.; Ahmed Maouloud, S.; Althueser, L.; Andrieu, B.; Angelino, E.; Angevaare, J. R.; Antochi, V. C.; Antón Martin, D.; Arneodo, F.; Baudis, L.; Baxter, A. L.; et al. (The European physical journal. C, Particles and fields, 2024)
The precision in reconstructing events detected in a dual-phase time projection chamber depends on an homogeneous and well understood electric ﬁeld within the liquid target. In the XENONnT TPC the ﬁeld homogeneity is achieved through a double-array ﬁeld cage, consisting of two nested arrays of ﬁeld shaping rings connected by an easily accessible resistor chain. Rather than being connected to the gate electrode, the topmost ﬁeld shaping ring is independently biased, adding a degree of freedom to tune the electric ﬁeld during operation. Two-dimensional ﬁnite element simulations were used to optimize the ﬁeld cage, as well as its operation. Simulation results were compared to 83mKr calibration data. This comparison indicates an accumulation of charge on the panels of the TPC which is constant over time, as no evolution of the reconstructed position distribution of events is observed. The simulated electric ﬁeld was then used to correct the charge signal for the ﬁeld dependence of the charge yield. This correction resolves the inconsistent measurement of the drift electron lifetime when using different calibrations sources and different ﬁeld cage tuning voltages.